Where and when? How phenological patterns of armyworm moths (Lepidoptera: Noctuidae) change along a latitudinal gradient in Brazil. Issue 4 (20th November 2018) - Piovesan, M.; Carneiro, E.; Specht, A.; Casagrande, M.M.
Abstract: The phenological patterns exhibited by different organisms are known as adaptive responses to the cyclical environmental conditions. However, only a limited number of researches explore which factors are responsible for these phenological patterns in pest species. In the current study, abundance patterns were studied in the phenology of three Spodoptera Guenée, 1852 species, along the 29° latitudinal gradient in South America. The goal was to test whether widely distributed and abundant crop pest species would exhibit different phenological responses to seasonal meteorological variables and host plant availability. To test this, 13 light traps were set up in Brazil to collect adult Spodoptera samples at the time of the new moon, every month, from June 2015 to May 2016. The time of occurrence and intensity of the phenology were determined for each species, employing circular statistics. Both metrics revealed significant variations among the different species, as well as the factors associated with them. Latitude was found to affect the period of occurrence in Spodoptera cosmioides (Walker, 1858) and Spodoptera albula (Walker, 1857), whereas in Spodoptera frugiperda (J. E. Smith, 1797) its effect was evident only in the intensity of its phenology. Further, both meteorological variables and host plant availability in the sampling sites produced predictive models to account for the phenological patterns expressed. These findings suggest that different species of Spodoptera exhibit different adaptive strategies in their life cycles in response to environmental conditions, thus necessitating specific management practices regarding their seasonal population fluctuation.